Analisis Faktor-Faktor yang Mempengaruhi Penerimaan dari Sektor Pariwisata Pantai Timur Sumatera Utara - Sinaga, Depo Lestari; Sirojuzilam, Sirojuzilam; Syafii, M. (Ekonomis: Journal of Economics and Business, 2024)
This research aims to analyze the influence of the number of restaurants, hotel room occupancy rates, number of foreign tourist visits, and population on the level of labor absorption on the East Coast of North Sumatra. Then to analyze the influence of the number of restaurants, hotel room occupancy rates, number of foreign tourist visits, population, labor absorption rate on tourism sector revenues on the East Coast of North Sumatra. As well as to analyze the influence of the number of restaurants, hotel room occupancy rates, number of foreign tourist visits, population on tourism sector revenues through the level of labor absorption on the East Coast of North Sumatra. The type of research used is associative research with a quantitative approach. The data used in this research are data on the number of restaurants, hotel room occupancy rates, number of foreign tourist visits, population, and regional income from the tourism sector on the East Coast of North Sumatra with a total of 12 regencies/cities for the 1-4 quarter period of 2012- 2021 taken from the North Sumatra Central Statistics Agency (BPS) with the analysis technique used is path analysis. The research results show that the number of restaurants, hotel room occupancy rates, number of foreign tourist visits, and population have a direct positive influence on the level of employment in the tourism sector on the East Coast of North Sumatra. The number of restaurants, hotel room occupancy rates, number of foreign tourist visits, population, and labor absorption rates have a direct positive influence on tourism sector revenues on the East Coast of North Sumatra. The number of restaurants, hotel room occupancy rates, number of foreign tourist visits, and population not have a direct influence on tourism sector revenues on the East Coast of North Sumatra through the level of labor absorption.